Analisis Perhitungan Pajak Penghasilan Badan Pada PT. XYZ Tahun 2017 - Michelle Natasya, Purnamawati Helen Widjaja (Jurnal Paradigma Akuntansi, 2021)
The country's biggest source of income is currently from the taxation sector, especially Corporate Income Tax. The purpose of this research is to find out whether the calculation of Income Tax and the fiscal profit / loss statement compiled by the Company is in accordance with the applicable tax provisions in Indonesia. The method used in this research is descriptive method. The subject in this research is PT. XYZ and the object is Financial Statements during 2017. Data collection methods used are interviews, observation and literature research. The results of the research showed that there was an error in preparing the fiscal financial statements so that the Income Tax payable was not in accordance with the applicable tax provisions in Indonesia.